2023
DOI: 10.1039/d3ta01850d
|View full text |Cite
|
Sign up to set email alerts
|

A baby step in assembling and integrating the components of an artificial photosynthesis device with forced heterojunctions towards improved efficiency

Abstract: How to achieve unassisted, economical, scalable, and sustainable artificial photosynthesis to liquid fuels/products with improved solar-to-fuel efficiency (STFE), to address carbon-neutral economy remains a big question. To a large degree,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Thus far, many semiconductor photocatalysts have been addressed with visible active properties, but the actual key to achieving solar-to-chemical energy conversion with >10% solar-to-fuel efficiency is combining them physically and electrically in an appropriate manner forming heterojunctions with wide bandgap semiconductors to make them useful in visible light active photocatalysis. 24…”
Section: Photocatalytic Hydrogen Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, many semiconductor photocatalysts have been addressed with visible active properties, but the actual key to achieving solar-to-chemical energy conversion with >10% solar-to-fuel efficiency is combining them physically and electrically in an appropriate manner forming heterojunctions with wide bandgap semiconductors to make them useful in visible light active photocatalysis. 24…”
Section: Photocatalytic Hydrogen Generationmentioning
confidence: 99%
“…pH conditions are yet to explore area for water splitting reactions, since water splitting reactions are limited to acidic pH only and not to basic scale. 153 Most recently, Salgaonkar et al 24 demonstrated a complete idea on the synthesis of BiVO 4 quantum dot (BVQD)-integrated TiO 2 by the SILAR (successive ionic layer adsorption and reaction) approach and prepared a thin-film photocatalyst of 1 cm 2 area over FTO by the doctor blade approach [as shown in Fig. 48] that showed 31–38% solar-to-fuel efficiency (STFE) with a photon-to-chemical conversion TOF of 2.73 s −1 , which was further used as a mimicking artificial leaf for the conversion of CO 2 + H 2 O to some value-added products (VAPs).…”
Section: Construction Of Panelsmentioning
confidence: 99%
“…4d). Product quantication was carried out by employing KHP as an internal standard 6,46 in the test solution.…”
Section: Electrocatalytic Performance With Oers/gorsmentioning
confidence: 99%
“…2 These challenges seeking possible solutions for clean-energy production without damaging the climate are looming large currently, and they need to be answered soon. 3,4 Recently, Domen's group 5 reported a proof of concept for the promising utilization of sunlight for water splitting; similarly, Salgaonkar et al 6 reported a proof of concept for artificial photosynthesis of methanol and formaldehyde from CO 2 in direct sunlight. Utilizing water as a bulk and cheap feedstock with power generated through Si-PV has attracted attention to address the green hydrogen issue through water electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome the aforementioned issues, numerous modifications such as metal-ion doping, , composite formation with other metal oxides, and heterojunction with other semiconducting materials have been explored. TiO 2 when combined with p-type semiconductor metal oxides, such as Fe 2 O 3 , Co 3 O 4 , NiO, and Cu x O, , extended light absorption to a wider wavelength range which is possible with enhanced charge separation. In the category of transition metal oxides, Cu x O is a favorable candidate to be used as a cocatalyst with TiO 2 in photocatalytic application due to its ability to absorb visible light from the solar spectrum, narrow band gap, and well-matched electronic band structures with TiO 2 .…”
Section: Introductionmentioning
confidence: 99%